Implementasi Cooperative Script Dalam Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Aqidah Akhlaq Kelas VIII di MTs Al-Ma’rif Kereak Pandan Indah - Fahrurrozi Fahrurrozi (LP3M IAI Al Urwatul Wutsqo Jombang, 2022)
This research was conducted because the development of science is growing, coupled with the existence of increasingly modern technology. Thus the teaching and learning process will also experience changes, both from the methods used and from the enthusiasm of students. This certainly affects students' understanding and learning outcomes. The purpose of this study was to find out how to implement a cooperative script in Aqidah Akhlaq subjects in improving the understanding of class VIII students at MTs Al-ma'rif Kereak Pandan Indah, and to find out whether the implementation of cooperative scripts in Aqidah Akhlaq subjects could improve students' understanding in class. VIII at MTs Al-ma'rif Kereak Pandan Indah. While the research method in this study uses classroom action assessment (CAR). The location of this research is at MTs Al-ma'rif Kereak Pandan Indah class VIII. In collecting data, this research uses daily notes and observations. The results of this study can be seen that the way of implementing cooperative scripts is in the early stages including: 1) subject teachers prepare lesson plans, 2) prepare test questions and answers, 3) prepare observation sheets, and in student learning outcomes have increased starting from pre test, post test cycle I, to post test cycle II. It can be seen from the average score of 78 students (pre test) increased to 86 (post test cycle I), and increased again to 95 (post test cycle II). Keywords: Implementation of Cooperative Script, student understanding, Akidah Akhlaq